Determinan Penyerapan Anggaran Badan Pengelolaan Keuangan dan Aset Daerah - Ananda, Tiara Syifa Putri; Maria, Maria; Sari, Yuliana (E-Jurnal Akuntansi; Vol 32 No 11 (2022), 2022)
This study aims to examine the components that influence the level of budget absorption in the Regional Financial and Asset Management Agency (BPKAD) of Palembang City.   The research population is employees who play a role in the process of preparing and implementing the budget at BPKAD Palembang City using a saturated sample consisting of PPK, PPTK, Treasurer, Secretariat Section, Budget Section, Asset Section and Accounting Section with a total of 51 people.   Data analysis used multiple linear regression techniques with SPSS software.   The research findings show that planning, HR competencies and external pressures have an effect on budget absorption while procurement documents have no effect.   Simultaneously these four components affect budget absorption by 38%.   The implications of this research can be considered in managerial decision making when planning, managing and implementing budgets. Keywords: Budget Absorption; Planning; Procurement Documents; Human Resources Competence; External Pressure